Causes of climate change - Malik, Ashok (New Delhi Rajat Publications, 2022)
The increase in the emission of green house gases and the subsequent enhanced greenhouse effect is the root of this problem, and the human activities and processes which cause these are quite comprehensively discussed. Trends in the increase in the concentrations of these green house gases are detailed with the use of tables and graphs, and pie charts have also been included to show the contribution of different gases to global warming.

The scientific chemical processes to show the production of these gases, also find cover here further illustrations and photographs to ascertain the impact of these gases are also included. In addition the consequences of the actions of these causes are discussed and critical insights into combating these causes are listed.
The Science of Climate Change – Causes of Global Climate Change – Ozone Depletion – International Carbon Market – Global Warming – Sea Level Rise – Effects of Climate Extremes – International Emission Trading – Climate Change and Health – Impacts of Climate Change to Coral Reefs – Climate Change and Adaption – Climate Change Mitigation – International Effort against Climate Change.
Includes bibliographical references and index
Keywords: Global environmental change; Climate change mitigation -- International cooperation